Ketahanan Plasma Nutfah Kapas terhadap Hama Pengisap Daun, Amrasca biguttula (ISHIDA) - IGAA. Indrayani; Siwi Sumartini (Buletin Plasma Nutfah, 2012)
Resistance of Cotton Germplasms Against Sucking Insect Pest, Amrasca biguttula (ISHIDA). IGAA. Indrayani and Siwi Sumartini. Morphological characteristics of cotton leaf have an important role on the resistance against sucking insect pest. Among the characters, leaf hair density is the most important in preventing the attack of sucking insect and it can be used to identify the resistance of cotton germplasms against sucking insect pest, A. biguttula. Study on resistance of cotton germplasms against sucking insect pest, A. biguttula (Ishida) was carried out at Asembagus Experimental Station of Indonesian Tobacco and Fiber Crops Research Institute (IToFCRI) in Malang from January to December 2009. The objective of study was to find out resistant cotton germplasms to A. biguttula. Fifty accessions of cotton germplasm were used as treatment and arranged in Randomized Block Design (RBD) with three replications. Plot size used was 10 m x 3 m that consists of two rows of tested accession and one row of Tamcot SP 37 as an atractant plant for A. biguttula. Parameters observed were leaf hair density, length of hair, population of A. biguttula nymph, and plant damage. Cotton accessions with higher hair density and length of leaf hair significantly reduced the frequency of action threshold population of A. biguttula and plant damage. Eleven cotton accessions, viz., SATU 65; VAR 78443; Sukothai 14; GM5U/4/2; Samir 730; L1; L4 x Rex/1; Paymaster 404; ISA 205B; Albar 72B; dan Tashkent 2 were showed more resistant to A. biguttula because of higher leaf hair density (121-360 hairs/cm2), lower nymph population (0-2 times of population threshold) and lower damage score (1.0-1.8). These cotton accessions could be promising to be genetic resources of resistance to sucking insect pest, A. biguttula. AbstrakKarakteristik morfologi daun kapas mempunyai peran penting pada ketahanan terhadap hama pengisap. Di antara sifat morfologi tersebut, kerapatan bulu daun sangat berperan dalam menghambat serangan pengisap sehingga sifat ini dapat digunakan untuk mengidentifikasi aksesi kapas yang tahan A. biguttula. Penelitian ketahanan aksesi kapas terhadap hama pengisap, A. biguttula dilakukan di KP. Asembagus Balai Penelitian Tanaman Tembakau dan Serat mulai Januari hingga Desember 2009. Penelitian ini bertujuan untuk mendapatkan aksesi kapas tahan A. biguttula. Sebanyak 50 aksesi kapas digunakaan sebagai perlakuan yang masing-masing disusun dalam Rancangan Acak Kelompok (RAK) dengan tiga kali ulangan. Ukuran petak adalah 10 m x 3 m yang terdiri atas 2 baris aksesi yang diuji dan 1 baris Tamcot SP 37 sebagai tanaman penarik A. biguttula. Parameter yang diamati adalah kerapatan (jumlah) bulu daun, panjang bulu daun, populasi nimfa A. biguttula, dan skor kerusakan tanaman. Aksesi dengan kerapatan bulu daun yang tinggi dan berbulu panjang secara nyata menurunkan frekuensi pencapaian populasi ambang kendali dan kerusakan tanaman. Sebelas aksesi kapas dengan jumlah bulu berkisar 121-360 helai/cm2, populasi nimfa rendah (frekuensi ambang rendah, 0-2 kali) dan skor kerusakan rendah (1,0-1,8) adalah SATU 65; VAR 78443; Sukothai 14; GM5U/4/2; Samir 730; L1; L4 x Rex/1; Paymaster 404; ISA 205B; Albar 72B; dan Tashkent 2. Aksesi ini berpotensi sebagai materi genetik untuk ketahanan terhadap A. biguttula.